Forward-Thinking: How a Century Ago Protecting Women and Children in the Workplace Laid the Groundwork for Gender Medicine and Decent Work - Riva, Michele Augusto; Paladino, Maria Emilia (La Medicina del Lavoro, 2025)
Dr. Livia Lollini, a physician and an early pioneer in women’s occupational health, authored a paper published as the lead article in the inaugural issue of La Medicina del Lavoro, which adopted its current title in 1925. Her work, La protezione della donna e del fanciullo sul lavoro (The Protection of Women and Children at Work), constitutes one of her contributions to labor protections for women and children in early 20th-century Italy. Born into a family distinguished by socialist and feminist ideals, she completed her medical education in 1913. Subsequently, she served as an assistant at the Clinica del Lavoro in Milan, where she addressed various issues related to occupational health. Drawing from international labor laws, Dr. Lollini critiqued the inadequate enforcement of existing legislation in Italy and emphasized the notable disparities in maternity protections. Her analysis highlighted the need to safeguard women’s health at the workplace and called for systemic reforms, including implementing regular medical examinations, female labor inspectors, and industrial nursing services. Her work, grounded in gender-sensitive approaches to occupational health, continues to resonate with contemporary principles of gender medicine. Although substantial advancements in labor legislation have been realized, many of the challenges she addressed—such as child labor, maternity rights, and workplace safety—remain central to global discussions surrounding decent work and equitable labor practices.